The Consolidated Framework for Implementation Research: Application to Education - William Walters; Wendy Barber; Mickey Jutras (Education Sciences)
This study investigates the application of the Consolidated Framework for Implementation (CFIR) in an educational setting. Although education implements numerous interventions and programs at all levels, standardized testing has primarily measured their success, leaving a paucity of direct measures for non-academic program implementation. Borrowing from an established practice in medicine, the CFIR, which provides a framework to identify potential barriers and facilitators to program implementation, is reviewed and investigated as a possible tool for use in education. Researchers applied the CFIR to a program intervention implemented at two Canadian university faculties of education. Through the complex coding and analysis inherent to the CFIR, barriers and facilitators were identified for program implementation. Reviewing and applying the CFIR provided results about the educational intervention and the use of the CFIR in education. While complex and time-consuming, the results suggest that the CFIR is a credible tool for measuring the effectiveness of implementing myriad educational initiatives at all system levels.